Combination of Controlled Release Platelet‐Rich Plasma Alginate Beads and Bone Morphogenetic Protein‐2 Genetically Modified Mesenchymal Stem Cells for Bone Regeneration. Issue 4 (1st April 2016) - Fernandes, Gabriela; Wang, Changdong; Yuan, Xue; Liu, Zunpeng; Dziak, Rosemary; Yang, Shuying
Abstract : Background: Platelet‐rich plasma (PRP) consists of platelet‐derived growth factor and transforming growth factor‐β that increase proliferation of mesenchymal stem cells (MSCs), whereas bone morphogenetic protein‐2 (BMP2) promotes osteogenic differentiation of MSCs. However, the high degradation rate of fibrin leads to the dissociation of cytokines even before the process of bone regeneration begins. To the best of the authors' knowledge, this is the first study to examine the combined effect of sustained release of PRP from alginate beads on BMP2‐modified MSC osteogenic differentiation in vitro and sustained release of PRP alone on a fracture defect model ex vivo as well as its effect on calvarial suture closure. Methods: After optimizing the alginate concentration for microspheres, the combined osteogenic and mineralization effect of PRP and BMP2 on MSCs was studied. Self‐setting alginate hydrogel carrying PRP was tested on a femur defect model ex vivo. The effect of PRP at day 15 on the closure of the embryonic mouse calvaria sutures ex vivo was also studied. Results: Increase of PRP concentration promoted proliferation of MSCs, and 2.5% to 10% of PRP gradually increased alkaline phosphatase (ALP) activity in the cells in a dose‐dependent manner. Sustained release of PRP and BMP2 demonstrated significantly higher ALP and mineralization activity ( P <0.05). Radiographs of alginate hydrogel with PRP‐treated bone demonstrated nearly complete healing of the fracture, and histologic sections of the embryonic calvaria revealed that PRP leads to suture fusion. Conclusion: Sustained release of PRP along with BMP2‐modified MSCs can significantly promote bone regeneration.